2009
DOI: 10.1080/09593980802622669
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of stroke survivors and apparently healthy individuals in southwestern Nigeria

Abstract: Quality of life (QoL) data have been used to assess treatment outcomes and to guide programme and rehabilitation efforts. QoL data in stroke survivors (SSV) from Nigeria are rare. This study compared the QoL of 84 SSV and 87 matched apparently healthy individuals (AH) in southwestern Nigeria. The effect of poststroke duration (PSD) on QoL and the relationship between QoL and motor performance (MP) were also investigated. SSV were recruited from all (7) tertiary health institutions in southwestern Nigeria. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…It also shows that people's perceptions might not reveal the true state of the individual. This corroborates previous findings that quality of life cannot be measured from external factors because it is all about individual experience (Wilk, 1999;Akinpelu and Gbiri, 2009;. It also supports the summation of Diener and Suh (1997) that objective quality may not reflect people's experience of wellbeing; therefore, it should be assessed separately from subjective quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It also shows that people's perceptions might not reveal the true state of the individual. This corroborates previous findings that quality of life cannot be measured from external factors because it is all about individual experience (Wilk, 1999;Akinpelu and Gbiri, 2009;. It also supports the summation of Diener and Suh (1997) that objective quality may not reflect people's experience of wellbeing; therefore, it should be assessed separately from subjective quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported the quality of life of individuals with psychiatric disorders and other chronic illnesses (Viitanen et al, 1988;King, 1996;Kwa et al, 1996;Cummins, 1997;Duncan et al, 1997;Sacco, 1997;Wyller et al, 1998;Claussen, 2004;Akinpelu and Gbiri, 2009;Cadilhac et al, 2010;Owolabi, 2010). A few of these have drawn comparisons between the quality of life of various chronically ill persons, and also compared them with apparently healthy individuals (Viitanen et al, 1988;Duncan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, rigorous research is lacking on the QOL and long-term outcomes of stroke survivors. Many previous studies of QOL in stroke survivors are limited by an absence of controls, a lack of standardisation of outcome scales, and selection bias due to patients only being recruited from hospitals [12,19,20]. Due to limited resources, high rates of early post-stroke mortality, and individual health beliefs, a large proportion of African stroke patients do not reach a hospital [21].…”
Section: Introductionmentioning
confidence: 99%
“…The participants received physiotherapy [13,15,16,17,18,19,20,21,22] emergency medical services [17,20], routine medical services [16,23], occupational therapy [13], and speech therapy [13]. This therefore implies that physiotherapy plays a vital role in stroke rehabilitation in Africa.…”
Section: African Stroke Survivorsmentioning
confidence: 99%